Shakespeare and the Demonization of Fairies - Spyra, Piotr (Text Matters: A Journal of Literature, Theory and Culture, 2017)
The article investigates the canonical plays of William Shakespeare - Hamlet, Macbeth, A Midsummer Night’s Dream and The Tempest - in an attempt to determine the nature of Shakespeare’s position on the early modern tendency to demonize fairy belief and to view fairies as merely a form of demonic manifestation. Fairy belief left its mark on all four plays, to a greater or lesser extent, and intertwined with the religious concerns of the period, it provides an important perspective on the problem of religion in Shakespeare’s works. The article will attempt to establish whether Shakespeare subscribed to the tendency of viewing fairies as demonic agents, as epitomized by the Daemonologie of King James, or opposed it. Special emphasis will also be put on the conflation of fairies and Catholicism that one finds best exemplified in Thomas Hobbes’ Leviathan. The article draws on a wealth of recent scholarship on early modern fairies, bringing together historical reflection on the changing perception of the fairy figure, research into Shakespeare’s attitude towards Catholicism and analyses of the many facets of anti-Catholic polemic emerging from early modern Protestant discourse.